One-way hash function construction based on Chen-type hyper-chaotic system and key-stream - REN Hai-peng; ZHUANG Yuan (Tongxin xuebao)
A scheme of constructing one-way hash function based on Chen-type hyper-chaotic system and key-stream was proposed. In this scheme, the plain-text and the secret key were used as the initial values of two hyper-chaotic systems, these values were evolved in a hyper-chaotic way during a predefined period. The results of the evolution were quantified and iterated using key-stream iteration to confuse and diffuse the plain-text with the secret key. Then, the cipher block chaining mode was used to generate the 128bit hash value for the plain-text with arbitrary length. Theoretical analysis and experimental results indicate that the proposed algorithm can satisfy the required security performance, such as data compression function, irreversibility, initial value sensitivity forgery resistance and collision resistance. Compared with some existing methods, the proposed scheme possesses better collision resistance performance.